Pengaruh Iklim Organisasi Dan Budaya Kerja Terhadap Komitmen Kerja Guru Sekolah Dasar Negeri Kecamatan Suruh Kabupaten Semarang - Daryati, Daryati; Nurkolis, Nurkolis; Wuryandini, Endang (Cetta: Jurnal Ilmu Pendidikan, 2025)
Teacher work commitment is an important variable in determining the performance and effectiveness of educational institutions that will encourage teachers to invest their energy and loyalty to the school and have a positive impact on teacher work commitment and the achievement of educational goals. The purpose of this study is to determine the influence of organizational climate and work culture together on work commitment. The research approach used is quantitative. This type of research uses correlation research. The population of this study was 281 teachers and the research sample was 165 teachers. Data collection was carried out using a questionnaire. The data analysis technique used in this study was descriptive data analysis, prerequisite tests including normality tests, multicollinearity tests, heteroscedasticity tests, linearity tests and hypothesis tests including simple and multiple linear regression. The results of the study showed that: (1) the correlation of organizational climate on work commitment was 0.685. The influence of organizational climate had a significant effect on the work commitment variable by 67.0%. (2) The correlation of work culture on work commitment was 0.860. The influence of work culture had a significant effect on the work commitment variable by 74.0%. (3) The significant influence of organizational climate and work culture on work commitment with the equation Ŷ = 15.860 + 0.187 X1 + 0.584 X2. Then the correlation coefficient value r is 0.889. The result of the coefficient of determination of the influence of variables X1 and X2 on Y is 79.0%.